Approach for MVL design based on armchair graphene nanoribbon field effect transistor and arithmetic circuits design. (October 2019) - Nayeri, Mahdieh; Keshavarzian, Peiman; Nayeri, Maryam
Abstract: This paper presents the approach for multiple-valued logic (MVL) design and implementing the arithmetic circuit based on armchair graphene nanoribbon field effect transistors (GNRFETs). For this purpose, the values of the threshold voltages are obtained for GNRFETs for utilizing in MVL. The Id -Vgs curve is drawn for all n-type GNRFETs by Synopsys HSPICE tools. Moreover, the width variations and band gap energy are scrutinized. The value of threshold voltage for range of N ​= ​3p+1 is more than N ​= ​3p. These observations exhibit that variation of the threshold voltages can be utilized for a circuit design based on GNRFET. Furthermore, the sub-threshold swing is obtained. As a proof of the concept, the ternary arithmetic circuits based on GNR are designed with 0.5 ​V supply voltage. The computational results confirm the threshold voltages values as well as the suitable figure of merits of using GNRFETs in multiple-valued logic circuit design.